Herd behaviour and market efficiency: evidence from the portuguese stock exchange - Braga, André Barreto das Neves de Almeida (2017)
This study examines herd behaviour in the Portuguese stock market by analyzing daily data from 2000 to 2016. To test for the existence of herding we use the cross sectional standard deviation and the cross sectional absolute deviation of returns as a measure of dispersion. According to rational asset pricing models equity return dispersion increases with market return but, if investors adopt an imitative behaviour the increasing linear relation between dispersion and market return will not be observable and, as a consequence, risk diversification becomes more difficult to accomplish. We find statistically significant evidence of herd behaviour during asymmetric market conditions, particularly during periods associated with positive returns. Furthermore we find supportive evidence for increased herding formation after the outbreak of the sovereign debt crisis. The findings also suggest that there is a contagion effect between the Spanish stock market and the Portuguese stock market regarding herding behaviour.